Ecological representativeness and total area protected by natural reserves in Ceará State, Brazil - Gomes, Francisco Vladimir Silva; Santos, Ana Maria Ferreira; Guerra, Renan Gonçalves Pinheiro; Queiroz, Liana Rodrigues; Menezes, Marcelo Oliveira Teles; Moro, Marcelo Freire (Sociedade & Natureza, 2022)
Among the targets of the Aichi Accord, of which Brazil was a signatory, was the commitment to protect at least 17% of its terrestrial and continental waters and 10% of all marine and coastal areas by 2020. When the target window closed, Brazil had 30% of those projected continental and 27% of the marine areas protected. Those areas, however, are unevenly distributed throughout the country, with the Amazon region exceeding 30% of the projected protection, while only approximately 8% of the Caatinga region has been considered. In this study, we computed the coverage of 98 designated Conservation Areas (CAs) and an ecological corridor in Ceará State (CE) and evaluated their distributions among that state’s various natural environments. Our results indicated that 92.6% % of the total officially protected areas corresponded to Uso Sustentável categories (US), which means sustainable use in English ,largely distributed among ecosystems outside the Caatinga domain, including coastal areas and humid and sub-humid enclaves. Those CAs contain rich bio- and geo-diversities of significant socioeconomic interest, although they do little to protect caatinga vegetation – the predominant ecosystem in the state. Additionally, the predominance of US CAs provide limited legal safeguards to biodiversity, especially among those CAs with low levels of legal protection, such as the category of Área de Proteção Ambiental (APA), which means Environmental Protection Areas in English , which account for the greatest coverage in the state. We conclude that the spatial configuration of state CAs is distant from ideal in terms of their extensions and representativeness, with few areas of protected caatinga vegetation and limited areas with full protection.